Protein degradability of oil cakes in rumen - Seven, Pinar Tatli; Azman, M. Ali (Indian Veterinary Journal, 2006)
The quantity and quality of-protein reaching:the small intestine are influenced by microbial protein synthesized in the rumen. This study was planned to determining. of degradability of crude protein (CP) fractions of soybean meal (SBM), cottonseed meal (CSM) and sun-flower meal (SFM) frequently used to prepare balanced rations Eastern Turkey.
Keywords: Degradation